Morphology development and mechanical properties of unsaturated polyester resin containing nanodiamonds. Issue 6 (13th March 2017) - Hashemi, Mohammadjafar; Shojaei, Akbar
Abstract: Unsaturated polyester/styrene (UP) resin was filled with nanodiamonds (NDs) containing carboxyl and methacrylate functionalities using mechanical mixing. Field emission SEM exhibited a uniform dispersion of tightly bound aggregates of nanosized spherical NDs with good interfacial interaction. Rheological measurements exhibited a step increment in the shear viscosity of a UP/ND suspension at 0.6 wt% ND resembling a percolation state at this loading. Shear viscosity data supported by dynamic mechanical analysis results suggested the development of effective ND particles in which ND aggregates were covered by only polyester macromolecules. Accordingly, the morphology of UP/ND composites approached a quasi‐percolation state at 0.6 wt% in which effective ND particles were connected thoroughly, instead of direct ND−ND contact, forming a co‐continuous polyester phase covering the ND particles. Based on such morphology, DSC and Fourier transform infrared analysis suggested the development of heterogeneous microgels in cured UP resin containing NDs which in turn governed the overall mechanical properties of the composites. © 2017 Society of Chemical Industry Abstract : Incorporation of nanodiamonds (NDs) in unsaturated polyester/styrene resin and increasing the content up to 0.6 wt% induced a quasi‐percolation morphology in which a co‐continuous polyester phase covering the ND particles was formed in the unsaturated polyester/styrene continuous matrix. Such morphology dominated the cure characteristics and mechanical properties of the unsaturated polyester/styrene resin.